2009
DOI: 10.1007/s12194-009-0057-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of scatter fractions for estimating leakage dose in medical X-ray imaging facilities

Abstract: It is essential to make accurate estimates of the scatter of radiation from the human body when calculating the leakage dose in medical X-ray imaging facilities. The scatter fraction varies with the size and shape of the radiation field in a way that is not exactly proportional to the area of the field. Japanese law quotes values for the scatter fraction that are provided by the National Council on Radiation Protection and Measurements, but these data were obtained 30 years ago, using equipment that differed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…Noto et al (2009), also observed this overestimate compared with their own measurements (the NCRP (2005), values are higher by a factor of 1.3 to 3 for an X-ray tube at 70 kV). It should be pointed out that the values of the NCRP (2005), result from an interpolation of various values from the literature for kinetic energies between 30 and 150 keV.…”
Section: Discussionmentioning
confidence: 74%
“…Noto et al (2009), also observed this overestimate compared with their own measurements (the NCRP (2005), values are higher by a factor of 1.3 to 3 for an X-ray tube at 70 kV). It should be pointed out that the values of the NCRP (2005), result from an interpolation of various values from the literature for kinetic energies between 30 and 150 keV.…”
Section: Discussionmentioning
confidence: 74%
“…Ο γενικός σκοπός της διατριβής αυτής, ήταν η χαρτογράφηση της δευτερογενούς ακτινοβολίας εντός ακτινολογικού θαλάμου σε συμβατικές ακτινολογικές μονάδες και η διέλευση αυτής από κοινά οικοδομικά υλικά για την αξιολόγηση αυτών ως προς την ακτινοπροστασία σε οδοντιατρικές και κτηνιατρικές εφαρμογές, με τη χρήση του απαιτούμενου μετρητικού εξοπλισμού [Edward et al 1965, Petrantonaki et al 1999, Noto et al 2003, Mc Vey et al 2004, Noto et al 2009. Η μέθοδος αναπτύχθηκε χρησιμοποιώντας συμβατική ακτινολογική μονάδα και το μετρητικό εξοπλισμό του Γενικού Νοσοκομείου Αττικής (Γ.Ν.Α) Σισμανόγλειο και του τμήματος Μηχανικών Βιοϊατρικής Τεχνολογίας ΤΕ του ΤΕΙ Αθηνών.…”
Section: περιληψηunclassified
“…In addition the inclusion of X-ray filtration, as an exposure parameter for 100 kVp tube voltage, can make the presented results applicable to clinical exposure conditions, like coronary angiography, whereby, added filtration and increased tube voltage is utilized for heavy patients. Furthermore, we also conduct a Monte Carlo Simulation analysis, where we simulate the production of the dose rate of secondary radiation [Noto et al 2003, Noto et al 2009.…”
Section: __________________________________ Quality Assurancementioning
confidence: 99%
See 2 more Smart Citations